A framework for understanding the website preferences of Egyptian online travel consumers. Issue 1 (2nd March 2015) - Yvette Reisinger, Dr Omar Moufakkir, Dr; Hagag, Wegdan; Clark, Lillian; Wheeler, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a framework for understanding issues affecting Egyptian online travel website preferences. Design/methodology/approach – Grounded theory was selected due to its suitability in generating frameworks from data gathered plus existing theory. Findings – The research describes the development of the electronic cultural adaptation framework (E-CAF), which consists of six theoretical dimensions that allow both researchers and practitioners to comprehend how Egyptian cultural values can affect their online travel shopping behaviour, in particular website design preferences. Research limitations/implications – The construction of the E-CAF is based on research into Egyptian online travel consumers. Development of the E-CAF could be expanded using participants from different cultural groups and other shopping domains. Practical implications – This research will help practitioners to understand how Egyptian cultural values can affect online behaviour and assist in developing strategies for local adaptations of online travel offerings. The framework will also provide web designers with guidelines for gathering and developing requirements from clients to implement culturally adaptive web interfaces for Egyptian consumers. Originality/value – While there are a number of existing cultural frameworks in existence, such as those of Hofstede, Hall, or Schwartz, these frameworks are not based on consumer behaviour, either online or offline, and are, therefore, not optimally suited for use in online marketing strategies or web design for Egyptian consumers. This research overcomes these limitations by providing a framework that recognises how cultural values can impact Egyptian consumer behaviour and provides a platform for further research, as well as online marketing strategies and tactics.